G561(P) Development of an asthma discharge plan for the Hampshire Hospitals NHS Foundation Trust. (27th April 2016) - Yianni, L; Struthers, S; Ilangovan, P
Abstract : Aims: The BTS Asthma Guidelines and NICE advise that patients discharged from hospital, following an exacerbation of their asthma, should have a personalised discharge plan. This forms part of patient education and self management. There is no standard action plan available for children currently. The lack of national guidance on designing discharge plans results in a wide variation in practice between hospitals. The BTS National Asthma Audit in 2014 identified that paediatric asthma patients at Royal Hampshire County Hospital were not routinely given an asthma discharge plan. Basingstoke Hospital had a discharge plan that needed updating. It was agreed that a HHFT-wide asthma discharge plan should be designed, agreed, implemented and re-audited. Methods: Discharge plans around the region were reviewed and compared with other NHS hospitals and international examples. An asthma discharge plan was then designed and developed by a working group and sent to a wider paediatric group for comment and modification. Whilst seeming straightforward, the process was slow and required repeated reviews and discussion. The discharge plan has a traffic light system, enabling parents to wean their child's bronchodilators, recognise deterioration, and take appropriate action. The plans are individual and can be tailored to meet patient's needs. Results: The asthma discharge plan was implemented in July 2015 and audited in November 2015, both locally and as part of the national asthma audit. User feedback was positive, stating that the plans are effective and simple to use. The use of th plans improves communication at discharge, whilst reducing time spent on typing individual discharge plans within the discharge summary. Learning points: It is important to follow national best practice and important for merged organisations to follow the same guidelines. Currently there are no national guidelines on designing individualised asthma discharge plans, resulting in wide variation in guidelines both locally and between hospitals. Gaining consensus across the two hospitals with different initial practice was difficult, but was achieved with persistence and using Delphi consensus strategies. A good result was achieved and is currently being implemented. A national asthma plan template would help standardise practice across UK hospitals.